SDH2 is involved in proper hypha formation and virulence in Candida albicans. (August 2018) - Bi, Shuang; Lv, Quan-Zhen; Wang, Tian-Tian; Fuchs, Beth Burgwyn; Hu, Dan-Dan; Anastassopoulou, Cleo G; Desalermos, Athanasios; Muhammed, Maged; Wu, Chin-Lee; Jiang, Yuan-Ying; Mylonakis, Eleftherios; Wang, Yan
Aim: To investigate the role of SDH2 in Candida albicans filamentation and virulence.Materials & methods: Caenorhabditis elegans and mouse candidiasis models were used to assess the virulence of a sdh2Δ/Δ mutant. Various hypha-inducing media were used to evaluate the hyphal development of C. albicans . DCFH-DA was used to measure intracellular Reactive Oxygen Species (ROS) levels.Results: The sdh2Δ/Δ mutant was avirulent in the C. elegans model, hypovirulent in a murine candidiasis model, and defective to form filaments both in vitro and in vivo . Intracellular ROS level increased in the sdh2Δ/Δ mutant, and the filamentation defects of sdh2Δ/Δ were rescued by decreasing intracellular ROS.Conclusion: SDH2 plays an important role in C. albicans filamentation and virulence probably through affecting intracellular ROS.